The epidemiology of noise exposure in the Australian workforce - Warwick Williams (Noise and Health, 2013)
This work considers an alternate methodology for the estimation of the noise exposed population of the Australian workforce. Previous methods relied on the statistics from the annual rate of application for worker′s hearing loss compensation claims, the generalization of small scale surveys to the broader population or larger scale telephone surveys. This proposed method takes measured noise exposure data from sampled industries and combines that with official demographic information on the numbers employed in the respective industries. From the Australian data, it is estimated that around 20.1% of the workforce regularly work in noise above the recommended exposure standard (L Aeq, 8 h = 85 dB) and 9.4% above and exposure of 90 dB. These figure lie within the range of estimates derived from other methodologies.